Uniform Accounting Manual for the Electrical Manufacturing Industry (Book). - Krebs, William S.; Cannon, Arthur M. (The Accounting Review, 1952)
Reviews the book "Uniform Accounting Manual for the Electrical Manufacturing Industry."